MicroRNA Detection by DNA‐Mediated Liposome Fusion. (15th January 2018) - Jumeaux, Coline; Wahlsten, Olov; Block, Stephan; Kim, Eunjung; Chandrawati, Rona; Howes, Philip D.; Höök, Fredrik; Stevens, Molly M.
Abstract: Membrane fusion is a process of fundamental importance in biological systems that involves highly selective recognition mechanisms for the trafficking of molecular and ionic cargos. Mimicking natural membrane fusion mechanisms for the purpose of biosensor development holds great potential for amplified detection because relatively few highly discriminating targets lead to fusion and an accompanied engagement of a large payload of signal‐generating molecules. In this work, sequence‐specific DNA‐mediated liposome fusion is used for the highly selective detection of microRNA. The detection of miR‐29a, a known flu biomarker, is demonstrated down to 18 nm within 30 min with high specificity by using a standard laboratory microplate reader. Furthermore, one order of magnitude improvement in the limit of detection is demonstrated by using a novel imaging technique combined with an intensity fluctuation analysis, which is coined two‐color fluorescence correlation microscopy. Abstract : FRET/don't FRET ! A new biomimetic sensor for microRNA is developed based on a liposome fusion mechanism. The presence of miR‐29a, a flu biomarker, triggers fusion between DNA‐functionalized liposomes, which can be monitored by an increase in FRET signal. The liposome fusion events offer high selectivity and can detect nanomolar concentrations of miR‐29a.